Semiotika Umberto Eco Dalam Representasi Perempuan Film Animasi Disney Raya and the Last Dragon - Fadhilla, Annisa Nurul; ismandianto, ismandianto (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2023)
Film is one of the most developed and dynamic forms of mass communication, using various advanced technology devices that are capable of creating animated films. Film is not only used as a medium of entertainment and pleasure, but also can be used to describe the reality that occurs in the real world, including the way women are portrayed. Disney Raya and the Last Dragon film described women as independent, tough, and able to struggle without being accompanied by men, and is different from how women are usually portrayed. This study aims to determine how the representation of women in Disney Raya and the Last Dragon film. This research is a qualitative research using semiotic analysis of Umberto Eco, and feminine and masculine categories according to BSRI. The results show that the representation of women in this film are shown in the appearance, expression, dialogue, gestures, and attitudes, which show the characters of Raya and Namaari who are tough, intelligent, and able to lead and make decisions. And Based on the feminine and masculine categories according to BSRI, various characters found in this film are masculine characters such as act as a leader, competitive, independent, and willing to take risks, while feminine characters are shown in afficionate characters, sympathetic, and yielding.